Impact of altruism on Filipino young adult volunteers' subjective well-being: The role of relatedness, autonomy and competence - Mangampat, Danica Mae L. (Animo Repository, 2022)
Altruism has been studied by several researches that it is linked with a positive experience of subjective well-being. To explain this phenomenon, it is hypothesized that the fulfillment of the basic psychological needs (i.e., the need for autonomy, competence, and relatedness) mediates their relationship. Altruistic behavior paves way for the satisfaction of these needs which further increases positive feelings towards oneself. A total of 190 young adults aged 20-29 who had volunteer activities for the past 5 years participated in the study to determine their experiences. Results suggest that the overall satisfaction of the three basic psychological needs mediate the relationship between altruism and SWB. However, in an in-depth parallel mediation analysis that investigated the individual contributions of each need in the model, results reveal that only Autonomy and Competence significantly and partially mediate the relationship between the volunteers’ altruism and SWB. 9.2% of the effect of altruistic tendencies on subjective well-being is mediated by the autonomy, while 15.2% is mediated by competence. Interestingly, relatedness is not a significant mediator of the three. The reason for this is that despite the social aspect of volunteer work in connecting with the recipients, the need to relate with others of Filipino young adult volunteers is not satisfied in volunteerism. However, they see this as an opportunity to be effective members of the society by selflessly offering their own efforts at their own volition.